New emergent therapies for atopic dermatitis: A review of safety profile with respect to female fertility, pregnancy, and breastfeeding. Issue 1 (5th November 2020) - Napolitano, Maddalena; Ruggiero, Angelo; Fontanella, Giuseppina; Fabbrocini, Gabriella; Patruno, Cataldo
Abstract: Atopic dermatitis (AD) is a chronic relapsing inflammatory skin disease. Systemic treatment is usually mandatory in moderate‐to‐severe AD of the adult; these patients need to be informed about safe and effective management of AD also regarding the reproduction. Treating a pregnant woman with AD with systemic drugs may affect the unborn child. While effects of traditional systemic treatments for AD on female fertility, pregnancy, and breastfeeding are largely known, data about new emergent therapies for AD are still poor. Treating pregnant or lactating women with AD can be a challenge since no large clinical studies on its possible effects and side‐effects on conception, pregnancy, the unborn child and lactation are currently available for new AD treatments.